Relato de Rhizoctonia solani AG-4 HG I em crisântemo (Papiro Branco e Amarelo) e R. solani AG-4 HG III em gipsófila no estado de São Paulo, Brasil, e sua patogenicidade cruzada - Bueno, César Júnior; Bettiol, Wagner; Mesa, Edisson Chavarro [UNESP]; Ceresini, Paulo Cézar [UNESP] (Grupo Paulista de Fitopatologia, 2013)
Currently, anastomosis groups (AG) of Rhizoctonia sp. on chrysanthemum and occurrence of this fungus on gypsophila have not been reported in Brazil. However, in the present study, normal and cross pathogenicity and sequencing of ITS-5.8S rDNA regions were used to confirm the AG of isolate of Rhizoctonia sp. obtained from chrysanthemum (White Papyrus) and from gypsophila plants cultivated in Holambra / São Paulo, Brazil. After these tests, it was confirmed the report of Rhizoctonia solani AG-4 HG I on chrysanthemum (White and Yellow Papyrus) and R. solani AG-4 HG III on gypsophila in the São Paulo state, Brazil, and also their cross pathogenicity.

Atualmente, grupamento de anastomose (AG) de Rhizoctonia sp. em crisântemo e ocorrência deste fungo em gipsófila ainda não foram relatados no Brasil. Assim, realizou-se teste de patogenicidade normal e cruzada e sequenciamento da região ITS-5.8S rDNA para identificar o AG de isolado obtido de plantas de crisântemo (Papiro Branco) e de gipsófila, ambas originárias de Holambra / São Paulo, Brasil. Após os testes, relata-se pela primeira vez a ocorrência de R. solani AG-4 HG I em crisântemo (Papiro Branco e Amarelo) e R. solani AG-4 HG III em gipsófila, no estado de São Paulo, Brasil, e, também, a sua patogenicidade cruzada.
Report of Rhizoctonia solani AG-4 HG I on chrysanthemum (White and Yellow Papyrus) and R. solani AG-4 HG III on gypsophila in the São Paulo State, Brazil, and their cross pathogenicity
Keywords: ornamental; fungo de solo; patogenicidade; Chrisanthemum spp; ornamental; soilborne phytopathogenic fungi; pathogenicity; Chrisanthemum spp